Advancements in Multi-Factor Authentication: A Quantum-Resilient and Federated Approach for Enhanced Security - Nur Syahrina Binti Juni; Grasila Huney Wan; Siti Aisyah Nabilah Binti Banchi; Estella Blessings; Venetha A/P Loganathan; Muhammad Faisal (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
The Internet of Things (IoT) phenomenon is centered around linking various devices and objects to the Internet, enabling them to communicate, collect, and exchange data [1]. The IoT needs strong, lightweight, and secure authorization schemes to regulate many devices with varying levels of ability. Quantum-resilient federated Multi-Factor Authentication (QRF-MFA) is a solution presented in this paper to address the above-discussed issues. Featuring quantum-resistant cryptographic protocols, high-speed and low-energy Physically Unclonable Functions (PUFs), decentralized identity management, and optimized communication protocols, QRF-MFA provides a complete solution for secure cross-domain device identification and authentication. This is done by leveraging blockchain technology for immutable and transparent management of identities yet limiting on-chain storage overhead. It also provides secure, lightweight communication well-suited for resource constrained IIoT devices, and it is designed for fog and edge computing environments as well. QRF-MFA eliminates the challenges of current methods by combining security, efficiency, and scalability and delivering a resilient and future-ready solution to secure IIoT authentication.